Are you inclined into agribusiness? perspectives from graduating students / Liyana Izzati Ismail, Mohd Nazir Rabun and Ain Insyiraah Mohd Ali Nopiah - Ismail, Liyana Izzati; Rabun, Mohd Nazir; Mohd Ali Nopiah, Ain Insyiraah (Universiti Teknologi MARA, 2020)
This study examines the level of graduating students' inclination to venture into agribusiness. The study also tries to examine and measure the relationships between knowledge, attitude, social environment, and level of graduating students' inclination to venture into agribusiness. In this study, 158 students of Bachelor of Science Technology and Plantation Management (AT220) at UiTM Cawangan Melaka, Kampus Jasin, Melaka were selected as respondents from the population of Faculty of Plantation and Agrotechnology. This study used the quantitative method as the best way to address the issue of the new generation's intention towards the agribusiness sector in Malaysia. In the quantitative method, stratified and convenience sampling techniques were employed as a data collection method. The first finding indicated that the students had a high level of inclination to venture into agribusiness. The second findings reported that there were positive significant relationships between knowledge, attitude, social environment, and agribusiness intention. These findings provide insight to the government officials in the Ministry of Agriculture and Agro-based Industries to resolve unemployment issues and achieve successful economic growth through the agriculture sector. The results obtained offer several key implications for increasing our understanding of factors related to students’ intention to venture into agribusiness. It may able to overcome the issue of the unemployment rate by creating more job opportunities for the new generations in Malaysia. Thus, universities play an important role in creating young agricultural entrepreneurs which is a crucial issue in this country. Implications and conclusions are also discussed.